Accelerating rare events using temperature programmed molecular dynamics: a review. Issue 14 (13th October 2019) - Shivpuje, Saurabh; Jaipal, Methary; Chatterjee, Abhijit
ABSTRACT: Uncovering the atomic scale mechanisms and their rate constants is often the first step towards understanding the dynamical behaviour of a material. Over the years, the molecular dynamics (MD) method has been a reliable workhorse by providing such kinetic information. However, when atomic scale events happen rarely at timescales accessible to MD it is more useful to apply a MD-based rare-event acceleration technique. We review a rare-event acceleration technique called the Temperature Programmed MD (TPMD). TPMD has been particularly effective with thermally-activated rare events on corrugated energy landscapes. Several fundamental aspects of the TPMD method are discussed including the temperature programme, deconvoluting the TPMD output to recover the rate constants for kinetic pathways, reconstructing unbiased dynamical trajectories from TPMD, as well as new schemes to optimise TPMD calculations. Sample scripts demonstrating the implementation of TPMD using the LAMMPS package, source codes for analysis, and user instructions have been provided.